The influence of repeated heat treatments on the propagation of fatigue cracking of medium carburized steel / Majid Khaleel Najem ... [et al.] - Najem, Majid Khaleel; Sultan, Jamal Nayief; Karash, Emad Toma; M. Ali, Adel; A. Ibrhim, Hssein (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
The issue of metal fatigue emerged as one of the major issues in a variety of engineering designs, and the design engineers were forced to take metals' fatigue resistance into account. In this paper, multiple quenching mediums and varied heat treatments were utilized to examine the effects of various heat treatments on the development of fatigue cracking in steel. The model that was carburized, quenched in distilled water and tempered before being quenched once more in distilled water and tempered a second time had the best outcomes, the fewest cycles needed to cause the model to fail, and a correlation between the rate of fatigue crack propagation and the length of the crack, according to the results. Additionally, the analytical findings demonstrated that this model, as opposed to models with fixed stress intensity factors, has a fatigue crack growth rate. The model that was carburized, quenched in coolant, then tempered and quenched again without performing the tempered appearance failed very rapidly. The high rate of the stress intensity factor with fatigue crack propagation is shown by the data analysis. The results show a reduction in the growth amount tendency of fatigue crack in the linear region mode-III.